Outcomes of Emergency Laparotomy in Pregnant and Postpartum Patients - Asif Mehmood, Bushra Nabi, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Emergency laparotomy in pregnancy and the postpartum period is a rare but dangerous surgical procedure with high morbidity and mortality of both the mother and the fetus. The timely surgical decision-making is usually complicated by physiological changes of pregnancy, diagnostic uncertainty, and delayed presentation, especially in resource-limited settings. Objective: To assess the indications, maternal outcomes, fetal outcomes and factors that can lead to adverse outcomes in case of emergency laparotomy during pregnancy and postpartum patients. Methods: A retrospective observational study was undertaken in a Khalifa Gul Nawaz Teaching Hospital Bannu, Pakistan and analyzed medical records of patients between March 2023 and August 2023. Pregnant women and postpartum patients (six weeks after delivery) who had an emergency laparotomy were all included. Descriptive and inferential statistics were used to analyze data on demographics, indications of surgery, perioperative findings, maternal complications, and fetal results. Results: There were 96 patients (58 (60.4) of them pregnant and 38 (39.6) postpartum). The most frequent presenting sign was acute appendicitis in the pregnant patients, with intestinal obstruction and puerperal sepsis being the most common in the postpartum patients. There were 29 patients with maternal complications (30.2), the most common being surgical site infection and sepsis. Maternal mortality was 4.2%. Adverse fetal outcomes were seen in 31.0% of pregnant patients and mainly preterm birth and fetal distress. Better outcomes were linked with early surgical intervention and a healthy mother condition. Conclusion: The use of emergency laparotomy in pregnant and postpartum patients poses huge maternal and fetal risks, especially when it is late and when the fetus develops sepsis. The diagnosis, early surgery and multidisciplinary approach are important to achieve better results in this population that is vulnerable. Keywords: Laparotomy in case of emergency; Pregnancy; Post partum period; Maternal and fetal outcomes.